Pengembangan Modul Ajar Elektronik dengan Memadukan Technological Pedagogical Content Knowledge (TPACK) sebagai Upaya Penguatan Domain Pengetahuan Peserta Didik Kelas V SD - Ariyanti, Sonia Shafana; Chan, Faizal; Budiono, Hendra (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to develop an electronic teaching module by combining Technological Pedagogical Content Knowledge (TPACK) as an effort to strengthen the knowledge domain of 5th grade elementary school students, and to determine the feasibility of an electronic teaching module by combining Technological Pedagogical Content Knowledge (TPACK) as an effort to strengthen the knowledge domain of class students 5 elementary school. The model in this research is the DDD-E (decide, design, develop, evaluate) development model. This research was carried out at SD Negeri 55/I Sridadi with the research subjects being teachers and grade 5 students. Research data was obtained through material validation, language validation, as well as media validation and teacher response questionnaires and student questionnaires. Data was analyzed qualitatively and quantitatively. The research results show that teaching modules that combine Technological Pedagogical Content Knowledge (TPACK) as an effort to strengthen the knowledge domain of 5th grade elementary school students are feasible to implement in the learning process.